Foamed tea powder embedded porous formaldehyde absorbing material and preparation method thereof

By embedding the porous formaldehyde absorbing material of tea powder in foam, using physical-chemical synergistic adsorption, the problems of slow formaldehyde absorption rate and unenvironmental materials in the prior art are solved, and efficient and environmentally friendly formaldehyde absorption effect is achieved.

CN119869462APending Publication Date: 2025-04-25HUAQIAO UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510054166.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-14
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The prior art has problems such as slow absorption rate, large energy consumption, unenvironmental protection and inability to use continuously when dealing with formaldehyde pollution in the room, and the effect of photocatalytic materials is limited by light conditions.

Method used

A foam-embedded tea powder porous formaldehyde absorption material is used. This material combines the porous structure of tea and foamy alginate carrier to significantly improve the formaldehyde absorption efficiency through physical-chemical synergistic adsorption.

Benefits of technology

It has achieved efficient absorption of formaldehyde, and the materials are green and environmentally friendly, low cost, and simple preparation. They are suitable for large-scale production, and the absorption efficiency is less restricted by environmental conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119869462A_ABST
    Figure CN119869462A_ABST
Patent Text Reader

Abstract

The invention discloses a foamy tea powder embedded porous formaldehyde absorbing material and a preparation method thereof, the foamy tea powder embedded porous formaldehyde absorbing material comprises a foamy alginate carrier and tea powder uniformly loaded in the foamy alginate carrier, the foamy alginate carrier is made of calcium alginate or aluminum alginate, and the mesh number of the tea powder is 50-200. According to the foamed tea powder-embedded porous formaldehyde absorbing material disclosed by the invention, through a physical-chemical synergistic adsorption effect, the porous structure and the adsorption characteristic of tea are combined with a foamed porous alginate carrier material. Therefore, the contact area between the effective components and external formaldehyde pollution is greatly increased, the high formaldehyde absorptivity is maintained, meanwhile, the method has the advantages of being environmentally friendly, low in material cost, simple and convenient in preparation method and the like, the method is suitable for large-scale production, and the absorption efficiency is less restricted by environmental conditions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of air purification materials, and particularly relates to a foam-like porous formaldehyde absorbing material for embedding tea powder and a preparation method thereof. Background Art

[0002] Formaldehyde is widely present in various interior decoration sites. It retains for a long time and is slowly released and continuously volatilized as a component of furniture adhesives, resulting in long-term high indoor formaldehyde concentrations and a long absorption and removal cycle.

[0003] Currently, activated carbon adsorption is the most widely used formaldehyde treatment method, but it has problems such as slow absorption rate, high energy consumption in the preparation process, lack of environmental protection, and inability to be used continuously. It usually takes several months and hundreds of kilograms of activated carbon to purify the environment, and the effect is not ideal.

[0004] The research by Li Wei et al. (Cai Xiaohong. Adsorption kinetics of formaldehyde by tea and tea product waste and development of environmentally friendly particleboard [D], 2010.) discovered an activated carbon-loaded TiO2 photocatalytic formaldehyde decomposition material, which effectively improved the adsorption performance of activated carbon for formaldehyde. However, the processing cost of this material is high and the metal resources are difficult to regenerate.

[0005] In view of the continuous volatilization of formaldehyde in actual application environments, He Taohong's research (He Taohong. Structural Regulation of Manganese Dioxide Catalysts and Study on Their Performance in Catalytic Decomposition of Formaldehyde [D], 2022.) proposed a new material that catalyzes the decomposition or oxidation of formaldehyde through manganese dioxide. This material can continuously absorb formaldehyde at a relatively fast rate, but there are problems with recycling pollution, high costs, and consumption of non-renewable resources. In addition, the effect of photocatalytic formaldehyde decomposition products is restricted by lighting conditions, and the time consumers stay indoors often overlaps with the time when they lose the catalytic effect, such as when sleeping at night. Summary of the invention

[0006] The present invention aims to overcome the defects of the prior art and provide a foam-like porous formaldehyde absorbing material for embedding tea powder.

[0007] Another object of the present invention is to provide a method for preparing the above-mentioned foam-like porous formaldehyde absorbing material encapsulating tea powder.

[0008] The technical solution of the present invention is as follows:

[0009] A foam-like porous formaldehyde absorbing material for embedding tea powder, comprising a foam-like alginate carrier and tea powder uniformly loaded in the foam-like alginate carrier, wherein:

[0010] The foam alginate carrier is made of calcium alginate or aluminum alginate.

[0011] The mesh size of tea powder is 50-200.

[0012] The preparation method of the above-mentioned foam-like porous formaldehyde absorbing material for embedding tea powder comprises the following steps:

[0013] (1) dissolving sodium alginate in purified water by heating and stirring in batches to obtain a sodium alginate solution;

[0014] (2) vacuum degassing the sodium alginate solution obtained in step (1);

[0015] (3) mixing the material obtained in step (2) with tea powder and filling the mixture into a mold, performing ultrasonic treatment at room temperature to make the mixture evenly distributed, and then freezing the mixture with liquid nitrogen;

[0016] (4) freeze-drying the material obtained in step (3) to obtain a foamy sodium alginate-tea powder mixture;

[0017] (5) preparing a calcium salt aqueous solution or an aluminum salt aqueous solution;

[0018] (6) soaking the foamy sodium alginate-tea powder mixture obtained in step (4) in the calcium salt aqueous solution or aluminum salt aqueous solution obtained in step (5) for heating reaction;

[0019] (7) After the material obtained in step (6) is fully washed, it is immersed in pure water and quickly frozen with liquid nitrogen for storage;

[0020] (8) freeze-drying the material obtained in step (7) to obtain the foam-like porous formaldehyde absorbing material encapsulating tea powder.

[0021] In a preferred embodiment of the present invention, in step (1), the heating temperature is 80-90°C.

[0022] In a preferred embodiment of the present invention, in step (1), the stirring speed is 200-1000 rpm.

[0023] In a preferred embodiment of the present invention, the concentration of the sodium alginate solution is 7.5-10 wt %.

[0024] In a preferred embodiment of the present invention, the vacuum degassing in step (2) has a pressure of less than or equal to 0.01 MPa and a time of 20-25 hours.

[0025] In a preferred embodiment of the present invention, in step (3), the mass ratio of the sodium alginate solution obtained in step (1) to the tea powder is 10:0.1-0.3.

[0026] In a preferred embodiment of the present invention, the solute of the calcium salt aqueous solution is calcium chloride, and the solute of the aluminum salt aqueous solution is aluminum sulfate.

[0027] Further preferably, the concentration of the calcium salt aqueous solution is 3-5wt%, and the concentration of the aluminum salt aqueous solution is 5-7wt%.

[0028] In a preferred embodiment of the present invention, in step (6), the heating reaction temperature is 42-47°C and the time is 8-12 min.

[0029] The beneficial effects of the present invention are:

[0030] 1. The foam-like embedded tea powder porous formaldehyde absorption material of the present invention combines the porous structure and adsorption characteristics of tea leaves with the foam-like porous alginate carrier material through physical-chemical synergistic adsorption. This not only greatly increases the contact area between the effective ingredients and the external formaldehyde pollution, but also has the advantages of being green and environmentally friendly, low material cost, and simple preparation method while maintaining a high formaldehyde absorption rate. It is suitable for large-scale production, and the absorption efficiency is less restricted by environmental conditions.

[0031] 2. The foam-like porous formaldehyde absorbing material for embedding tea powder prepared by the present invention is easy to process, suitable for large-scale production, and has the advantages of large specific surface area and excellent absorption performance. Unlike most solid chemical and physical adsorbents, these adsorbents are usually limited to surface absorption, and formaldehyde molecules are difficult to react in depth. The foam-like carrier prepared by the present invention provides an excellent structural basis for the mutual combination of formaldehyde and active substances, improves the utilization rate of the overall active substances of the material, and thus significantly increases its action life and absorption rate. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 These are actual photos of the foam-like porous formaldehyde absorbing materials encapsulating tea powder prepared in Examples 1 to 8 of the present invention. DETAILED DESCRIPTION

[0033] The technical solution of the present invention is further illustrated and described below through specific implementation modes in combination with the accompanying drawings.

[0034] Example 1

[0035] (1) Take 180g of pure water, heat it to 80-90°C, weigh 20g of sodium alginate and add it in five batches, 4g each time, and increase the shear stirring speed from 200rpm to 1000rpm evenly with the amount of sodium alginate added. When the sodium alginate added in the previous batch is completely swollen, immediately add the next batch of sodium alginate until all the sodium alginate is completely dissolved to obtain a sodium alginate solution;

[0036] (2) placing the sodium alginate solution obtained in step (1) in an atmosphere of 0.01 MPa for 24 hours to eliminate tiny bubbles therein;

[0037] (3) Take 20 g of the material obtained in step (2), add 0.6 g of 100-mesh tea powder thereto, mix well and fill into a mold of a specific shape, perform ultrasonic treatment at room temperature to make it evenly distributed, and then freeze with liquid nitrogen;

[0038] (4) freeze-drying the material obtained in step (3) for 48 hours to remove moisture and form a foamy sodium alginate-tea powder mixture;

[0039] (5) Take 96 g of pure water and 4 g of calcium chloride to prepare a 4% calcium chloride solution and control its temperature to 45° C. in advance;

[0040] (6) soaking the foamy sodium alginate-tea powder mixture obtained in step (4) in the calcium chloride solution obtained in step (5), maintaining the temperature at 45° C., and continuing the reaction for 10 minutes. Slightly pressing the foamy sodium alginate-tea powder mixture during the reaction to allow the foamy sodium alginate-tea powder mixture to absorb the calcium chloride and promote the internal reaction;

[0041] (7) washing the material obtained in step (6) with tap water and purified water in turn, then soaking it in purified water and rapidly freezing it with liquid nitrogen for storage;

[0042] (8) The material obtained in step (7) was freeze-dried for 48 hours to obtain Figure 1 The foam-like porous formaldehyde absorbing material encapsulating tea powder is shown.

[0043] Example 2

[0044] (1) Take 185 g of pure water, heat it to 80-90° C., weigh 15 g of sodium alginate and add it in five batches, 3 g each time, and increase the shear stirring speed from 200 rpm to 1000 rpm evenly with the amount of sodium alginate added. When the sodium alginate added in the previous batch is completely swollen, immediately add the next batch of sodium alginate until all the sodium alginate is completely dissolved to obtain a sodium alginate solution;

[0045] (2) placing the sodium alginate solution obtained in step (1) in an atmosphere of 0.01 MPa for 24 hours to eliminate tiny bubbles therein;

[0046] (3) Take 20 g of the material obtained in step (2), add 0.3 g of 100-mesh tea powder thereto, mix well and fill into a mold of a specific shape, perform ultrasonic treatment at room temperature to make it evenly distributed, and then freeze with liquid nitrogen;

[0047] (4) freeze-drying the material obtained in step (3) for 48 hours to remove moisture and form a foamy sodium alginate-tea powder mixture;

[0048] (5) Take 96 g of pure water and 4 g of calcium chloride to prepare a 4% calcium chloride solution and control its temperature to 45° C. in advance;

[0049] (6) soaking the foamy sodium alginate-tea powder mixture obtained in step (4) in the calcium chloride solution obtained in step (5), maintaining the temperature at 45° C., and continuing the reaction for 8 minutes. Slightly pressing the foamy sodium alginate-tea powder mixture during the reaction to allow the foamy sodium alginate-tea powder mixture to absorb the calcium chloride and promote the internal reaction;

[0050] (7) washing the material obtained in step (6) with tap water and purified water in turn, then soaking it in purified water and rapidly freezing it with liquid nitrogen for storage;

[0051] (8) The material obtained in step (7) was freeze-dried for 48 hours to obtain Figure 1 The foam-like porous formaldehyde absorbing material encapsulating tea powder is shown.

[0052] Example 3

[0053] (1) Take 180g of pure water, heat it to 80-90°C, weigh 20g of sodium alginate and add it in five batches, 4g each time, and increase the shear stirring speed from 200rpm to 1000rpm evenly with the amount of sodium alginate added. When the sodium alginate added in the previous batch is completely swollen, immediately add the next batch of sodium alginate until all the sodium alginate is completely dissolved to obtain a sodium alginate solution;

[0054] (2) placing the sodium alginate solution obtained in step (1) in an atmosphere of 0.01 MPa for 24 hours to eliminate tiny bubbles therein;

[0055] (3) Take 20 g of the material obtained in step (2), add 0.6 g of 100-mesh tea powder thereto, mix well and fill into a mold of a specific shape, perform ultrasonic treatment at room temperature to make it evenly distributed, and then freeze with liquid nitrogen;

[0056] (4) freeze-drying the material obtained in step (3) for 48 hours to remove moisture and form a foamy sodium alginate-tea powder mixture;

[0057] (5) Take 94 g of pure water and 6 g of aluminum sulfate to prepare a 6% aluminum sulfate solution and control its temperature to 45° C. in advance;

[0058] (6) soaking the foamy sodium alginate-tea powder mixture obtained in step (4) in the aluminum sulfate solution obtained in step (5), maintaining the temperature at 45° C., and reacting for 8 minutes, applying slight pressure to the foamy sodium alginate-tea powder mixture during the reaction to allow the foamy sodium alginate-tea powder mixture to absorb calcium chloride and promote internal reaction;

[0059] (7) washing the material obtained in step (6) with tap water, 1% sodium bicarbonate solution, tap water and purified water in sequence, then soaking in purified water and rapidly freezing with liquid nitrogen for storage;

[0060] (8) The material obtained in step (7) was freeze-dried for 48 hours to obtain Figure 1 The foam-like porous formaldehyde absorbing material encapsulating tea powder is shown.

[0061] Example 4

[0062] (1) Take 185 g of pure water, heat it to 80-90° C., weigh 15 g of sodium alginate and add it in five batches, 3 g each time, and increase the shear stirring speed from 200 rpm to 1000 rpm evenly with the amount of sodium alginate added. When the sodium alginate added in the previous batch is completely swollen, immediately add the next batch of sodium alginate until all the sodium alginate is completely dissolved to obtain a sodium alginate solution;

[0063] (2) placing the sodium alginate solution obtained in step (1) in an atmosphere of 0.01 MPa for 24 hours to eliminate tiny bubbles therein;

[0064] (3) Take 20 g of the material obtained in step (2), add 0.6 g of 100-mesh tea powder thereto, mix well and fill into a mold of a specific shape, perform ultrasonic treatment at room temperature to make it evenly distributed, and then freeze with liquid nitrogen;

[0065] (4) freeze-drying the material obtained in step (3) for 48 hours to remove moisture and form a foamy sodium alginate-tea powder mixture;

[0066] (5) Take 94 g of pure water and 6 g of aluminum sulfate to prepare a 6% aluminum sulfate solution and control its temperature to 45° C. in advance;

[0067] (6) soaking the foamy sodium alginate-tea powder mixture obtained in step (4) in the aluminum sulfate solution obtained in step (5), maintaining the temperature at 45° C., and reacting for 8 minutes, applying slight pressure to the foamy sodium alginate-tea powder mixture during the reaction to allow the foamy sodium alginate-tea powder mixture to absorb calcium chloride and promote internal reaction;

[0068] (7) washing the material obtained in step (6) with tap water, 1% sodium bicarbonate solution, tap water and purified water in sequence, then soaking in purified water and rapidly freezing with liquid nitrogen for storage;

[0069] (8) The material obtained in step (7) was freeze-dried for 48 hours to obtain Figure 1 The foam-like porous formaldehyde absorbing material encapsulating tea powder is shown.

[0070] Example 5

[0071] (1) Take 180g of pure water, heat it to 80-90°C, weigh 20g of sodium alginate and add it in five batches, 4g each time, and increase the shear stirring speed from 200rpm to 1000rpm evenly with the amount of sodium alginate added. When the sodium alginate added in the previous batch is completely swollen, immediately add the next batch of sodium alginate until all the sodium alginate is completely dissolved to obtain a sodium alginate solution;

[0072] (2) placing the sodium alginate solution obtained in step (1) in an atmosphere of 0.01 MPa for 24 hours to eliminate tiny bubbles therein;

[0073] (3) Take 20 g of the material obtained in step (2), add 0.48 g of 100-mesh tea powder thereto, mix well and fill into a mold of a specific shape, perform ultrasonic treatment at room temperature to make it evenly distributed, and then freeze with liquid nitrogen;

[0074] (4) freeze-drying the material obtained in step (3) for 48 hours to remove moisture and form a foamy sodium alginate-tea powder mixture;

[0075] (5) Take 96 g of pure water and 4 g of calcium chloride to prepare a 4% calcium chloride solution and control its temperature to 45° C. in advance;

[0076] (6) soaking the foamy sodium alginate-tea powder mixture obtained in step (4) in the calcium chloride solution obtained in step (5), maintaining the temperature at 45° C., and continuing the reaction for 10 minutes. Slightly pressing the foamy sodium alginate-tea powder mixture during the reaction to allow the foamy sodium alginate-tea powder mixture to absorb the calcium chloride and promote the internal reaction;

[0077] (7) washing the material obtained in step (6) with tap water and purified water in turn, then soaking it in purified water and rapidly freezing it with liquid nitrogen for storage;

[0078] (8) The material obtained in step (7) was freeze-dried for 48 hours to obtain Figure 1 The foam-like porous formaldehyde absorbing material encapsulating tea powder is shown.

[0079] Example 6

[0080] (1) Take 185 g of pure water, heat it to 80-90° C., weigh 15 g of sodium alginate and add it in five batches, 3 g each time, and increase the shear stirring speed from 200 rpm to 1000 rpm evenly with the amount of sodium alginate added. When the sodium alginate added in the previous batch is completely swollen, immediately add the next batch of sodium alginate until all the sodium alginate is completely dissolved to obtain a sodium alginate solution;

[0081] (2) placing the sodium alginate solution obtained in step (1) in an atmosphere of 0.01 MPa for 24 hours to eliminate tiny bubbles therein;

[0082] (3) Take 20 g of the material obtained in step (2), add 0.24 g of 100-mesh tea powder thereto, mix well and fill into a mold of a specific shape, perform ultrasonic treatment at room temperature to make it evenly distributed, and then freeze with liquid nitrogen;

[0083] (4) freeze-drying the material obtained in step (3) for 48 hours to remove moisture and form a foamy sodium alginate-tea powder mixture;

[0084] (5) Take 96 g of pure water and 4 g of calcium chloride to prepare a 4% calcium chloride solution and control its temperature to 45° C. in advance;

[0085] (6) soaking the foamy sodium alginate-tea powder mixture obtained in step (4) in the calcium chloride solution obtained in step (5), maintaining the temperature at 45° C., and continuing the reaction for 8 minutes. Slightly pressing the foamy sodium alginate-tea powder mixture during the reaction to allow the foamy sodium alginate-tea powder mixture to absorb the calcium chloride and promote the internal reaction;

[0086] (7) washing the material obtained in step (6) with tap water and purified water in turn, then soaking it in purified water and rapidly freezing it with liquid nitrogen for storage;

[0087] (8) The material obtained in step (7) was freeze-dried for 48 hours to obtain Figure 1 The foam-like porous formaldehyde absorbing material encapsulating tea powder is shown.

[0088] Example 7

[0089] (1) Take 180g of pure water, heat it to 80-90°C, weigh 20g of sodium alginate and add it in five batches, 4g each time, and increase the shear stirring speed from 200rpm to 1000rpm evenly with the amount of sodium alginate added. When the sodium alginate added in the previous batch is completely swollen, immediately add the next batch of sodium alginate until all the sodium alginate is completely dissolved to obtain a sodium alginate solution;

[0090] (2) placing the sodium alginate solution obtained in step (1) in an atmosphere of 0.01 MPa for 24 hours to eliminate tiny bubbles therein;

[0091] (3) Take 20 g of the material obtained in step (2), add 0.48 g of 100-mesh tea powder thereto, mix well and fill into a mold of a specific shape, perform ultrasonic treatment at room temperature to make it evenly distributed, and then freeze with liquid nitrogen;

[0092] (4) freeze-drying the material obtained in step (3) for 48 hours to remove moisture and form a foamy sodium alginate-tea powder mixture;

[0093] (5) Take 94 g of pure water and 6 g of aluminum sulfate to prepare a 6% aluminum sulfate solution and control its temperature to 45° C. in advance;

[0094] (6) soaking the foamy sodium alginate-tea powder mixture obtained in step (4) in the aluminum sulfate solution obtained in step (5), maintaining the temperature at 45° C., and reacting for 8 minutes, applying slight pressure to the foamy sodium alginate-tea powder mixture during the reaction to allow the foamy sodium alginate-tea powder mixture to absorb calcium chloride and promote internal reaction;

[0095] (7) washing the material obtained in step (6) with tap water, 1% sodium bicarbonate solution, tap water and purified water in sequence, then soaking in purified water and rapidly freezing with liquid nitrogen for storage;

[0096] (8) The material obtained in step (7) was freeze-dried for 48 hours to obtain Figure 1 The foam-like porous formaldehyde absorbing material encapsulating tea powder is shown.

[0097] Example 8

[0098] (1) Take 185 g of pure water, heat it to 80-90° C., weigh 15 g of sodium alginate and add it in five batches, 3 g each time, and increase the shear stirring speed from 200 rpm to 1000 rpm evenly with the amount of sodium alginate added. When the sodium alginate added in the previous batch is completely swollen, immediately add the next batch of sodium alginate until all the sodium alginate is completely dissolved to obtain a sodium alginate solution;

[0099] (2) placing the sodium alginate solution obtained in step (1) in an atmosphere of 0.01 MPa for 24 hours to eliminate tiny bubbles therein;

[0100] (3) Take 20 g of the material obtained in step (2), add 0.24 g of 100-mesh tea powder thereto, mix well and fill into a mold of a specific shape, perform ultrasonic treatment at room temperature to make it evenly distributed, and then freeze with liquid nitrogen;

[0101] (4) freeze-drying the material obtained in step (3) for 48 hours to remove moisture and form a foamy sodium alginate-tea powder mixture;

[0102] (5) Take 94 g of pure water and 6 g of aluminum sulfate to prepare a 6% aluminum sulfate solution and control its temperature to 45° C. in advance;

[0103] (6) soaking the foamy sodium alginate-tea powder mixture obtained in step (4) in the aluminum sulfate solution obtained in step (5), maintaining the temperature at 45° C., and reacting for 8 minutes, applying slight pressure to the foamy sodium alginate-tea powder mixture during the reaction to allow the foamy sodium alginate-tea powder mixture to absorb calcium chloride and promote internal reaction;

[0104] (7) washing the material obtained in step (6) with tap water, 1% sodium bicarbonate solution, tap water and purified water in sequence, then soaking in purified water and rapidly freezing with liquid nitrogen for storage;

[0105] (8) The material obtained in step (7) was freeze-dried for 48 hours to obtain Figure 1 The foam-like porous formaldehyde absorbing material encapsulating tea powder is shown.

[0106] The same mass of the foamy tea powder embedded porous formaldehyde absorbing material obtained in Example 1, the foamy tea powder embedded porous formaldehyde absorbing material obtained in Example 3 and the blank sodium alginate gel were placed in a sealed container with a volume of 250 mL, 240 μL of 1% formaldehyde solution and 0.5 g of calcium chloride were added, and a control group was set up, and the temperature was maintained at 25°C for 24 hours. After 24 hours, a 16 cm 2 Filter paper strips (2cm×8cm) were used to determine the amount of residual formaldehyde by measuring the time it took for potassium permanganate to completely fade.

[0107] Analyzing the results of the above determinations, when potassium permanganate reacts with formaldehyde at a certain concentration and amount of substance, the reaction rate depends on the formaldehyde concentration. According to the Lambert-Beer law, when the solution thickness is consistent, the color of the potassium permanganate solution is linearly related to its concentration, so the fading time is positively correlated with the residual formaldehyde concentration. When the residual formaldehyde concentration is high, the potassium permanganate test paper changes color quickly; when the residual formaldehyde concentration is low, the fading speed is slow. That is, the fading rate is negatively correlated with the absorbance. A fast color change rate indicates a low absorbance; a slow color change rate indicates a high absorbance.

[0108] The results of the measurement are shown in Table 1 below:

[0109] Table 1 List of experimental results of each control group

[0110]

[0111] The above description is only a preferred embodiment of the present invention, and therefore cannot be used to limit the scope of the present invention. That is, equivalent changes and modifications made according to the patent scope of the present invention and the contents of the specification should still fall within the scope of the present invention.

Claims

1. A foam-like porous formaldehyde absorbing material for embedding tea powder, characterized in that: It comprises a foamy alginate carrier and tea powder uniformly loaded in the foamy alginate carrier, wherein: The foam alginate carrier is made of calcium alginate or aluminum alginate. The mesh size of tea powder is 50-200.

2. The method for preparing a foam-like porous formaldehyde absorbing material for embedding tea powder according to claim 1, characterized in that: The steps include: (1) dissolving sodium alginate in purified water by heating and stirring in batches to obtain a sodium alginate solution; (2) vacuum degassing the sodium alginate solution obtained in step (1); (3) mixing the material obtained in step (2) with tea powder and filling the mixture into a mold, performing ultrasonic treatment at room temperature to make the mixture evenly distributed, and then freezing the mixture with liquid nitrogen; (4) freeze-drying the material obtained in step (3) to obtain a foamy sodium alginate-tea powder mixture; (5) preparing a calcium salt aqueous solution or an aluminum salt aqueous solution; (6) soaking the foamy sodium alginate-tea powder mixture obtained in step (4) in the calcium salt aqueous solution or aluminum salt aqueous solution obtained in step (5) for heating reaction; (7) After the material obtained in step (6) is fully washed, it is immersed in pure water and quickly frozen with liquid nitrogen for storage; (8) freeze-drying the material obtained in step (7) to obtain the foam-like porous formaldehyde absorbing material encapsulating tea powder.

3. The preparation method according to claim 2, characterized in that: In the step (1), the heating temperature is 80-90°C.

4. The preparation method according to claim 2, characterized in that: In the step (1), the stirring speed is 200-1000 rpm.

5. The preparation method according to claim 2, characterized in that: The concentration of the sodium alginate solution is 7.5-10 wt %.

6. The preparation method according to claim 2, characterized in that: The vacuum degassing pressure in step (2) is less than or equal to 0.01 MPa, and the time is 20-25 hours.

7. The preparation method according to claim 2, characterized in that: In the step (3), the mass ratio of the sodium alginate solution obtained in the step (1) to the tea powder is 10:0.1-0.

3.

8. The preparation method according to claim 2, characterized in that: The solute of the calcium salt aqueous solution is calcium chloride, and the solute of the aluminum salt aqueous solution is aluminum sulfate.

9. The preparation method according to claim 8, characterized in that: The concentration of the calcium salt aqueous solution is 3-5 wt %, and the concentration of the aluminum salt aqueous solution is 5-7 wt %.

10. The preparation method according to claim 2, characterized in that: In the step (6), the heating reaction temperature is 42-47° C. and the time is 8-12 min.